Efficient evaluation of member cardinality in cluster-based vehicular cyber-physical systems - Jin Qian; Tao Jing; Yan Huo; Hui Li; Zhen Li (International Journal of Distributed Sensor Networks)
In the cluster-based vehicular cyber-physical systems, the member cardinality is an important parameter for the cluster maintaining and updating. Also, it is widely utilized in the design of protocols for routing, medium access, activation scheduling, and topology control. However, the delay of the traditional member cardinality evaluation method is too large to satisfy the requirement of the high-dynamic vehicular cyber-physical systems. To tackle this problem, in this article, we propose a new member cardinality evaluation method that is based on the time slot occupation technique. The new method can improve the evaluation efficiency and obtain a high evaluation accuracy. Besides, we extend the method to further improve the performance. Finally, we analyze the proposed method considering the unreliability of the channel state. The mathematical analysis and simulation results demonstrate the performance of the proposed method.